Risk Management Analysis Using the Enterprise Risk Management Method with Fintech as the Risk Controller: (Study at Yayasan Rabbunalloh Surabaya) - Zakariya, Novie Andriani; Hakim, Ahmad Khairul; Bramayudha, Airlangga; Ilham, Moh. (Proceedings of International Conference on Da'wa and Communication, 2022)
This study aims to determine the risks that occur in the Rabbunalloh foundation, analyze the risk management of the Rabbunalloh foundation and find out risk control through the use of fintech as a solution to the Rabbunalloh foundation. This research uses qualitative research methods. The type of primary data in the form of interview results is carried out through structured interviews. The informants in this study are several administrators, including the chairman of the foundation, persons in charge, and volunteers who participate in the foundation's risk management. The data analysis was carried out through a phenomenological approach using the Enterprise Risk Management (ERM) COSO framework. The results of this study found that (1) there are 15 risks in the Rabbunalloh foundation, namely 2 risks in collecting donations, 7 risks in digital technology, 3 risks in the management of the foundation, and 3 risks in reporting donations, (2) risk management at the Rabbunalloh foundation needs to be done properly based on the ERM Framework, (3) risk control in the Rabbunalloh foundation with the highest category, which can be done through the use of fintech with creating an IT-based reporting system on the website so that donors can directly report proof of donation transfer so that donation reports can be directly reported to the center.